Employment protection and takeovers - Dessaint, Olivier; Golubov, Andrey; Volpin, Paolo (Journal of Financial Economics, 2017)
Labor restructuring is a key driver of takeovers and the associated synergy gains worldwide. In a difference-in-differences research design, we show that major increases in employment protection reduce takeover activity by 14–27% and the combined firm gains (synergies) by over half. Consistent with the labor channel behind these effects, deals with greater potential for workforce restructuring show a greater reduction in volume, number, and synergies. Increases in employment protection impede layoffs, resulting in wage costs that match the magnitude of synergy losses. Offer prices are not fully adjusted, with both bidders and targets exhibiting lower returns following the reforms.